Optical analysis of a CMB cosmic string candidate. Issue 2 (22nd February 2019) - Sazhina, O S; Scognamiglio, D; Sazhin, M V; Capaccioli, M
Abstract: The complexity of the cosmological scenario regarding cosmic strings (CSs) stands still in the way of a complete understanding. We describe here a promising strategy for the possible detection of these elusive physical entities. It is based on the search of strong gravitational lensing events in the location area of the CS candidate (CSc-1), which was declared in a previous work by cosmic microwave background (CMB) analysis. Using photometric and geometric criteria, we identified pairs of candidates of lensed galaxies (LGCs) in the 'string field' (SF), which were then compared with the average density of background galaxy pairs in a set of 'control fields'. We found an excess of 22 per cent (per deg 2 ) of the LGCs in SF, which exceeds the estimated cosmic dispersion. We also found that the number of LGCs is in excess of 29.2 per cent in the angular separation bin [8, 9 arcsec]. Finally, we analysed the possibility of a preferred orientation of the line connecting the centres of the LGCs. The orientation is statistically significant for an angular separation bin [4, 6 arcsec]. Therefore, we found two 'windows' for the preferred angular separation for LGCs along the possible CS. However, the confirmation of the gravitational lensing origin of our LGCs requires spectroscopic observations that seem to be justified by the present results. We plan to acquire their spectra and to continue the study of the spectral and morphological features of the LGCs in the CSc-1 field and to analyse the other CS candidates using the same strategy.